2018
DOI: 10.1080/15592294.2018.1475980
|View full text |Cite
|
Sign up to set email alerts
|

DNMT1 modulates interneuron morphology by regulatingPak6expression through crosstalk with histone modifications

Abstract: Epigenetic mechanisms of gene regulation, including DNA methylation and histone modifications, call increasing attention in the context of development and human health. Thereby, interactions between DNA methylating enzymes and histone modifications tremendously multiply the spectrum of potential regulatory functions. Epigenetic networks are critically involved in the establishment and functionality of neuronal circuits that are composed of gamma-aminobutyric acid (GABA)-positive inhibitory interneurons and exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 158 publications
(222 reference statements)
3
41
0
Order By: Relevance
“…In agreement with the expression and DNA methylation analysis of POA-derived embryonic interneurons, elevated levels of Lhx1 expression were also detected upon Dnmt1 siRNA application in Neuro2a (N2a) cells, a cell culture model already applied in a previous study [12]. Of note, this increase in Lhx1 expression was not observed upon treatment with RG108, an inhibitor of DNA methylation (Figure 1(d)), which even leads to a significant decrease putatively by eliciting secondary effects.…”
Section: Dnmt1 Regulates the Expression Of Lhx1 Noncanonicallysupporting
confidence: 86%
See 3 more Smart Citations
“…In agreement with the expression and DNA methylation analysis of POA-derived embryonic interneurons, elevated levels of Lhx1 expression were also detected upon Dnmt1 siRNA application in Neuro2a (N2a) cells, a cell culture model already applied in a previous study [12]. Of note, this increase in Lhx1 expression was not observed upon treatment with RG108, an inhibitor of DNA methylation (Figure 1(d)), which even leads to a significant decrease putatively by eliciting secondary effects.…”
Section: Dnmt1 Regulates the Expression Of Lhx1 Noncanonicallysupporting
confidence: 86%
“…We have recently reported that the DNA methyltransferase 1 (DNMT1) orchestrates the post-mitotic maturation of POA-derived cortical interneurons by promoting their migratory morphology and survival in part through the modulation of Pak6 expression [27]. Of note, we found that Pak6 transcription is not regulated by DNMT1-dependent DNA methylation [12,27], but non-canonically through interactions of DNMT1 with histone methylating enzymes [12].…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…Moreover, it should be kept in mind that DNMT1 was described to act non-canonically on gene expression by interactions with histone modifiers (Symmank and Zimmer, 2017;Symmank et al, 2018). DNMTs and DNA methylation interfere at different levels with histone modifications, which likewise modulate the specificity of transcriptional changes.…”
Section: Dna Methylation and Dnmts In Interneuron Functionality In Hementioning
confidence: 99%